1996
DOI: 10.1080/15216549600201793
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the regulatory subunit of cAMP‐dependent protein kinase type II from human brain

Abstract: The regulatory subunit type II (RII) of cAMP‐dependent protein kinase purified from human brain was represented by two proteins with apparent molecular masses of 51‐52 kD and 54 kD. Dephosphorylation of human RII containing 3 mol phosphate/mol protein did not change the electrophoretic pattern. One‐dimensional peptide mapping of 51‐52 kD and 54 kD proteins after digestion with St. aureus V8 protease evidenced to their being distinct proteins. The data obtained permit to assume that human RII of neural type is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It is known that binding of cAMP of the R subunit of inactive cAMP‐dependent protein kinase leads to enzyme activation. MoAb used in the present study were previously shown to inhibit cAMP binding to the neural RII in vitro [1, 2]. So abolition of cAMP‐induced protein kinase activation in the presence of MoAb can indicate the formation of an immune complex.…”
Section: Resultsmentioning
confidence: 64%
See 4 more Smart Citations
“…It is known that binding of cAMP of the R subunit of inactive cAMP‐dependent protein kinase leads to enzyme activation. MoAb used in the present study were previously shown to inhibit cAMP binding to the neural RII in vitro [1, 2]. So abolition of cAMP‐induced protein kinase activation in the presence of MoAb can indicate the formation of an immune complex.…”
Section: Resultsmentioning
confidence: 64%
“…This concentration is comparable with 0.5 μM RII endogenous concentration [15]taking into account the leakage of ∼1/3 of the enzyme (B). The intracellular concentrations of RII and MoAb were enough for their association ( K d for MoAb 6 and the homologous antigen is equal to 3.8×10 −9 M [1]). Formation of the immune complex manifested itself in inhibition of cAMP binding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations